Insect Activities and their Impact on the Yield of Abelmoschus esculentus L ( Malvaceae) in Bambili ( Mezam - Cameroon) - Nadine, Otiobo Atibita Esther; Wirmai, Lukong Anmarie; Fotso; Awah, Tita Margaret; Nkuo-Akenji, Theresia (International Journal of Sustainable Agricultural Research, 2020)
Experiments were made to evaluate the impact of the flowering insect activity on Abelmoschus esculentus (L.) pod and seed yields. Their foraging and pollination activities were examined in Bambili from September 2019 to February 2020. Treatments included open ﬂoral access to all visitors (treatment 1) and bagging of ﬂowers to avoid all visits (treatment 2). Observations were made on 30 ﬂowers per treatment. The Insect foraging behavior, their rhythm of activity, the fruiting rate and the mean number of seeds per pod were recorded. The results show that three insect species visited A. esculentus flowers. Lipotriches collaris was the most common species with 76.40 %, followed by Apis mellifera (19.10%) and Musca domestica (4.49%). Insects foraged throughout the day light period. Their activity was highest between 9 am and 12 pm Insect species foraged the flowers for pollen and nectar. Comparing the yields of the two treatments, it appeared that insect visits increase the number of fruits per plant, the average number of seeds per fruit and the percentage of normal seeds by 42.27%, 17.39% and 22.88%. The maintenance of insect nest close to A. esculentus field is recommended to improve the seed production of okra.